Physical activity rates of male and female students from selected European physical education universities - Maciaszek, Janusz; Ołpińska-Lischka, Marta; Pospieszna, Barbara; Knisel, Elke; Honsová, Šárka; Epping, Roy; Bronikowski Michał (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Physical education teachers should promotephysical activity that is beneficial to health. It is assumed thatphysical education students as future physical education teacherswill have a high level of physical activity. Aim of Study. The aimof this study was to compare the level of physical activity (PA)in physical education (PE) students from different countries(Czech Republic, Germany, the Netherlands, and Poland) usingthe unified questionnaire (an IPAQ-based questionnaire withquestions adapted for this purpose). Material and Methods. Thestudy included a random selection of female and male (f = 131,m = 214) university students majoring in physical education.To measure the PA rate, the International Physical ActivityQuestionnaire – Long Form (IPAQ-LF) was used. Differencesbetween the groups were tested with ANOVA. Significancewas denoted by p < 0.05. Results. Comparison of intense PArates shows that the highest results were recorded for men andwomen studying in the Czech Republic, while the lowest oneswere for students from Poland and Germany. Considering theresults it was noted that male students have higher PA rates thanwomen. Only female students from Germany had a higher resultthan their fellow male students from Germany. Analysis ofdifferences in moderate PA undertaken by students showed thehighest activity level for both women and men studying in theNetherlands. Conclusions. We observed that nearly all femaleparticipants, except for the students from Germany, had a lowerlevel of intense PA than male participants. Identification of thereasons for differences in PA intensity between the sexes mighthelp eliminate the barriers and increase the level of PA in allcountries. We observed that social support may have indirectlypredicted the PA of students.
Keywords: physical activity; IPAQ; physical education; students; Europe